2014
DOI: 10.1186/1471-2407-14-574
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the underscreened women in developed countries: the value of HPV test

Abstract: BackgroundPoor attendance to cervical cancer (CC) screening is a major risk factor for CC. Efforts to capture underscreened women are considerable and once women agree to participate, the provision of longitudinal validity of the screening test is of paramount relevance. We evaluate the addition of high risk HPV test (HPV) to cervical cytology as a primary screening test among underscreened women in the longitudinal prediction of intraepithelial lesions grade 2 or worse (CIN2+).MethodsWomen were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
3
16
0
1
Order By: Relevance
“…We have now an ongoing program to actively identify this population [ 5 ]. A recent evaluation of this strategy [ 29 ] showed that underscreened women had a high burden of cervical disease. Attempts to extend these initiatives into an organized activity are undergoing [ 30 ] a randomized trial inviting these women to participate in the screening program.…”
Section: Discussionmentioning
confidence: 99%
“…We have now an ongoing program to actively identify this population [ 5 ]. A recent evaluation of this strategy [ 29 ] showed that underscreened women had a high burden of cervical disease. Attempts to extend these initiatives into an organized activity are undergoing [ 30 ] a randomized trial inviting these women to participate in the screening program.…”
Section: Discussionmentioning
confidence: 99%
“…The laboratories included were Hospital Universitario Dr. Josep Trueta, Consorcio hospitalario de Vic, Hospital Universitario Joan XXIII, Hospital del Mar, Hospital universitario de Bellvitge, Hospital de Granollers, Hospital de Althaia, and Laboratorio de Atención Primaria Dr. Robert. The main outcome was histological confirmation of cervical intraepithelial neoplasia grade 2 or worse (CIN2+) [ 10 , 11 ]. The risk of CIN2+ was evaluated following a Kaplan–Meier approaches.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of cotesting was performed on a group of 1,832 underscreened women with a mean age of 54.1 years (range 40–88 years) [ 10 ]. The majority (92.4%) had both negative screening tests and 338 women were recommended to stop screening for being over 65 years old with a negative cotesting.…”
Section: The Evaluation Of the Hpv Testmentioning
confidence: 99%
“…In the autonomous region of Catalonia, several actions have been implemented since 2006 to increase coverage of select populations [5]. Analysis of the Catalonian data has revealed poor regular attendance, of once screened women, and high prevalence of cervical lesions in women high poor screening history [67]. Some studies from Spain have reported that between 50–80% of women with invasive cervical cancer had not undergone cytology testing during the 10 years prior to their cancer diagnosis [810].…”
Section: Introductionmentioning
confidence: 99%